How to Combat Covid-19 Global Impacts - Gulam, Putli Noor Asikin Binti Datu; Razali, Faizzuddin; Vincent, Rosalind J.S; Singh, Harjinder Kaur Balbir; Ani, Fauziah; Mariappan, Uvathi; Rahman, Santibuana Abd (CENTRAL ASIA AND THE CAUCASUS, 2022)
Sheikh Lokeman Hazli Azali's thinking on the directions of Sufism needs to be examined in the middle of society not limited to his students but also to general public, educators, government officials, lecturers and others in order to combat Covid-19 global impacts. The study uses qualitative research methods through two approaches namely Historical approach and Islamic theory approach. In terms of Islamic theory approach, the author reveal the relevance of Sheikh Lokeman Hazli Azali’s thinking on the concept of Sufi in the twenty first century, whether there is a new theory presented or just the development of the concept of classical scholars that already exist, or compare it with contemporary scholarly figures. The ultimate aim is to study and examine what are the factors lead to Covid-19 global impacts, with the objective to analyse and identify the role of thinking on the directions of Sufism as a way to combat Covid-19 global impacts. From the research the findings it can be seen that Sheikh Lokeman Hazli Azali’s thinking and practice on the directions of Sufism did managed to combat Covid-19 global impacts. This study had also mentioned his contribution not only to combat Covid-19 global impacts but also to combat extremist, terrorist and others using the concept of Sufi itself.